Comparison of functional outcomes and complications of conservative management verses surgical fixation with a locking compression plate in the treatment of displaced middle third clavicular fracture - Sakharkar, Nilesh S.; Atram, Vikas A.; Arora, Chandan A.; Bhurre, Rohit K.; Atilkar, Akshay J.; Sakhare, Kuber (International Journal of Research in Orthopaedics, 2022)
Background: About 3 to 5 percent of all fractures are clavicle fractures, which account for 45 percent of fractures at the shoulder. While fractures of the lateral and medial thirds of the clavicle account for 15% and 5% of all clavicle fractures, respectively, middle third fractures account for 80% of all clavicle fractures. Methods: patients were divided into two groups at random. Patients selected for conservative treatment with figure of eight Clavicle Brace and arm sling/pouch were treated with the brace immediately and for surgical intervention with locking plating. Constant and Murley's scoring system was used to check for signs of healing and functional improvement Results: The 40 patients in the current study include 20 with a new fracture of the mid-third clavicle who underwent surgical treatment with clavicular locking compression plate and screws and 20 who underwent conservative treatment with a figure-eight clavicle brace and arm pouch/sling. There was a statistically significant difference in the Constant and Murley score between the surgical group and the conservative group. Conclusions: According to the present study, patients with a displaced mid-third clavicle fracture may benefit more from surgery than from conservative treatment.